(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This study explores the role of green banking in advancing Sustainable Development Goals (SDGs), with a particular focus on Central Asian countries. It examines how financial instruments such as green loans and green bonds contribute to sustainable economic and environmental outcomes. Using panel data from 2010 to 2023 and applying fixed effects regression models, the research provides empirical evidence that green finance significantly enhances SDG performance. Countries with more developed green financial systems, such as Kazakhstan and Uzbekistan, show higher SDG index scores, while nations with limited green finance infrastructure face slower progress. The study also finds that rising carbon emissions negatively impact SDG achievements, whereas GDP growth alone is insufficient without sustainable financial integration. The findings highlight the transformative potential of green banking and emphasize the need for stronger regulatory frameworks, regional cooperation, and institutional support to fully leverage green finance for sustainable development. This research contributes to the growing literature on sustainable finance and offers policy recommendations for integrating environmental priorities into national development strategies.